Analisis Program Kemitraan Bidan dan Dukun Bayi di Kota Jambi - Ruwayda Ruwayda; M Dody Izhar (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
Based on the results of the 2018 Riskesdas, the proportion of birth attendants in women aged 10 - 54 years still has 6.7% of pregnant women giving birth not with health workers. Aur Duri Health Center is one of the Puskesmas from 20 Puskesmas in Jambi City, which in 2018 occurred 1 death of pregnant women who were helped by TBAs in Penyengat Rendah Village, Telanai Pura Sub-District. This incident should not have happened considering the location of the Aur Duri Puskemas area was still in the Jambi City Center and access to health workers, health centers and hospitals was very smooth and easy to reach. There are still 12 traditional birth attendants in the work area of Aur Duri Health Center in 2018. This study aims to analyze the implementation of partnership programs for midwives and traditional birth attendants in the work area of Aur Duri Health Center, Jambi City: input, process and output variables. Data collection techniques used the method of in-depth interviews, Focus Group Discussion (FGD), and document review.Based on the results of the study it was known that the partnership between midwives and traditional birth attendants had not gone well, while the partnership between midwives and traditional birth attendants in the Aur Duri Community but there was no continuation of implementation of these activities. It is recommended that the Health Office and Aur Duri Puskesmas provide support and guidance and can allocate funds for partnership activities between midwives and traditional birth attendants so that it can be a solution to achieving KIA coverage targets, especially labor assistance by health workers and suppressing death cases. In addition, it is necessary to conduct monitoring and evaluation in the implementation of this partnership so that it can run well